1999
DOI: 10.1046/j.1365-2362.1999.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

High serum laminin concentrations in patients with Candida sepsis

Abstract: Laminin serum concentrations might be useful to differentiate nonbacterial, bacterial and fungal etiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…C. albicans also has an effect on BM proteins. Indeed, Presterl et al (1999) reported that laminin concentrations are significantly higher in patients with Candida sepsis than in patients with bacterial sepsis. The present study and others suggest that infections by C. albicans are initiated by adhesion and are mediated by binding to several ECM host proteins.…”
Section: Discussionmentioning
confidence: 99%
“…C. albicans also has an effect on BM proteins. Indeed, Presterl et al (1999) reported that laminin concentrations are significantly higher in patients with Candida sepsis than in patients with bacterial sepsis. The present study and others suggest that infections by C. albicans are initiated by adhesion and are mediated by binding to several ECM host proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Many species of the complex oral microbiota maintain a symbiotic relationship with the host (10)(11)(12). To maintain homeostasis within the oral cavity, the host has two distinct but interrelated immune response systems: the salivary immune system (13)(14)(15)(16) and the serum immune system (17,18). The changing balance of conditions in the mouth influences the stability and integrity of the oral mucosal tissues.…”
Section: The Oral Cavity Environmentmentioning
confidence: 99%